EFFECTIVENESS OF USING E-JOBSHEET MEDIA IN DIGITAL DESIGN COURSES - Saputri, Amelia Ajeng; Andayani, Sri Wahyu; Kartikasari, Enggar (Prosiding Pendidikan Teknik Boga Busana, 2023)
The aim of this research is to determine the effectiveness of using e-jobsheet media in digital design courses in the 2022/2023 academic PVKK FKIP UST Study Program. The population in this study was 61 students. Data collection techniques use questionnaires and documentation. The validity test results showed that 20 questions were tested on 24 respondents, all questions were declared valid. The results of the reliability test obtained a calculated reliability coefficient of 0.956 above the rtable value of 0.60, thus this data is classified as very reliable for use in collecting research data. The data analysis technique uses quantitative descriptive tests using mean, median, mode and standard deviation calculations. The research results show that: 1) Effectiveness in the quite effective category with a percentage of 66%. 2) Media engagement in the category is quite effective with a percentage of 72%. 3) Media clarity in the quite effective category with a percentage of 67%. 4) Completeness of media information in the quite effective category with a percentage of 67%. 5) Media access in the category is quite effective with a percentage of 64%. The use of e-jobsheet media in digital design courses in the PVKK UST study program for the 2022/2023 academic year is quite effective.